Agricultural inputs in Kenya: Demand, supply, and the policy environment - Kirimi, Lilian; Olwande, John; Langat, Jackson; Njagi, Timothy; Kamau, Mercy; Obare, Gideon (International Food Policy Research Institute, 2023)
Agricultural inputs, including fertilizers, seeds, breeding stock, crop protection chemicals, machinery, irrigation, and knowledge, are key to innovation and productivity improvement, and are the backbone of any agricultural revolution. They are an integral part of the food supply chain, which comprises the production and distribution of food, and as such a key component of the food system (HLPE 2017). The food supply chain involves various actors at different stages of the chain but this chapter focuses only on agricultural inputs, including both farm inputs and agricultural advisory services.